If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(z + 4) + -6z = 45 Reorder the terms: 7(4 + z) + -6z = 45 (4 * 7 + z * 7) + -6z = 45 (28 + 7z) + -6z = 45 Combine like terms: 7z + -6z = 1z 28 + 1z = 45 Solving 28 + 1z = 45 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-28' to each side of the equation. 28 + -28 + 1z = 45 + -28 Combine like terms: 28 + -28 = 0 0 + 1z = 45 + -28 1z = 45 + -28 Combine like terms: 45 + -28 = 17 1z = 17 Divide each side by '1'. z = 17 Simplifying z = 17
| 7x+8=3x+28 | | 7y+2+5y-11y=-8-2 | | 2(4p-1)-4(2p-8)-8p= | | 2(4p-1)-4(2p-8)-8= | | 18bc-24bc= | | 18bc-8y= | | 225=98-w | | -v+289=105 | | 16y-8y= | | 4x+1=5x-6 | | 15x+21y= | | 4y/7=5y/2 | | x/4=9/20 | | 8x=2(4x-5)-2 | | (3x)(92x)=13 | | 8-2(3-2x)=2(x-1) | | 2+4x=5x-6 | | 2(2x+17)=178 | | (2x+3y)3= | | 10(3)= | | 5x+6=30+2x | | (X^2+2x-1)(3x-2)= | | (x^2+2x-1)*(3x-2)= | | tan=sin^2 | | 3x+x-1.5x=4 | | y+-2=y | | 8*x=100 | | (2x+3y)(2x+3y)(2x+3y)= | | 4+x=4x | | 0/√7xy | | 2x^2+3x+1.5=0 | | 3x[3+2x(32-10)]=71 |